Current Situation of the Integration of Neutrosophy in Requirements Engineering - Franklin Parrales-Bravo; Roberto Tolozano-Benites; Leonel Vasquez-Cevallos; Leili Lopezdominguez-Rivas (Neutrosophic Sets and Systems)
This study conducts a comprehensive literature review to explore the integration of neutrosophic logic in Requirements Engineering (RE), addressing challenges such as uncertainty, ambiguity, and conflicting stakeholder perspectives. By systematically analyzing peer-reviewed studies from 2015 to 2024, the research synthesizes existing neutrosophic techniques—including Type-2 Neutrosophic Numbers (T2NNs), Neutrosophic Cognitive Maps (NCMs), and Single-Valued Neutrosophic Sets (SVNS)—and categorizes their applications into uncertainty handling, conflict resolution, and requirement prioritization. The study highlights neutrosophy’s transformative potential in enhancing RE practices, offering robust solutions beyond traditional methods. Additionally, it identifies underexplored techniques like Bipolar Neutrosophic Sets (BNS) and Neutrosophic Rough Sets (NRS) for future research, underscoring neutrosophy’s role as a paradigm shift in managing RE complexities.